A novel sub-step composite implicit time integration scheme for structural dynamics - Wen, W.B.; Wei, K.; Lei, H.S.; Duan, S.Y.; Fang, D.N. (Computers & structures, 2017)
•Desirable computation accuracy (including Amplitude Decay (AD), Period Elongation (PE)).•Good numerical dissipation/dispersion characteristics when compared with other schemes (applicable for wave propagation analysis).•Desirable computation efficiency when compared with other typical schemes. In this paper, a novel sub-step composite implicit time integration scheme is presented for solving the problems in structural dynamics. The proposed scheme possesses desirable stability and accuracy. With appropriate algorithmic parameter value, the scheme can attain controllable amplitude decay and period elongation. Effectiveness of the proposed scheme is tested in some example solutions by comparing with other well-known implicit schemes. Theoretical analysis and numerical simulations demonstrate that the proposed scheme possesses high computation efficiency as well as desirable numerical dissipation characteristics.